Opposing Viewpoints on Youth Social Media Banning in the U.S. for the Combatance of Extremist Recruiting: Constitutionality and Societal Implications - West, Lindsay A; Martin, Richard V; Perkins, Courtney; Quatel, Jennifer M; Macgregor-Skinner, Gavin (International journal of cyber warfare and terrorism, 2016)
Today, terrorist groups are recruiting, inspiring, and guiding global strategies not just by Internet operations, but through an organized, steady infusion of propaganda videos and call-to-action messages. Most worrisome: increasing evidence that the youth population represents a particularly susceptible cohort, being drawn into the ranks of terrorist organizations operating worldwide. In response, this article will address the pros and cons of social media banning, its effects on constitutional rights, and its effectiveness towards decreasing radicalization and recruitment. The research presented here aims to further the field of Homeland Security and to encourage debates on how to decrease terrorism and youth recruitment and whether banning social media would assist the Department of Homeland Security's mission. In conclusion, this article explores both sides of the spectrum while offering insight for scholars, organizations, and practitioners regarding the attainability of social media banning in the United States.